Prevalence and Associated Risk Factors of Cervical Human Papillomavirus (HPV) Infection among Women in Northcentral Nigeria: A cross-sectional study - Abigail Zakka; Christianah Ayolabi; Babatunde Olusola; Tenny Egwuatu (Babcock University Medical Journal, 2023)
Objective: This study aimed to determine the prevalence of cervical HPV infections and its associated socio-demographic risk factors among women attending selected hospitals in some parts of Northcentral Nigeria.